Evaluating the Impact of School-Based Management Committees on Infrastructure Development in Junior Secondary Schools in Yobe State, Nigeria - J, Tika T.; Sani, Emmanuel; Ibanga, Isaac John (Darul Yasin Al Sys, 2024)
This study evaluates the impact of school-based management committees on infrastructure development in junior secondary schools in Yobe State, Nigeria. Two research questions and two hypotheses were formulated and tested at a 0.05 level of significance. A structured questionnaire was used to collect relevant data from the respondents. The population of the study was 1503 comprising Teachers and members of School-Based Management Committees (SBMC). The sample size of the study was 350 and a random sampling technique was employed using lucky dip to select 12 participating schools for this study. The research questions were answered using mean and standard deviation and a t-test was used to analyze the hypotheses at 0.05 level of significance. The finding of this study established that there is no significant difference between the teachers and members of SBMC on the challenges and strategies of SBMCs in the provision of infrastructure at Yobe State Junior Secondary School. The study established that There was no significant difference between the mean rating of teachers and members of SBMC on the roles of SBMCs in the provision of infrastructure Yobe State Junior Secondary School. This study recommended that SBMCs at the school level should endeavor to work hard in mobilizing members of their communities. Sanctions and punishment for the non-involvement of SBMC in the school’s activities like monitoring and evaluation, supervision of school activities, and School administrators should continue to work hard and maximize their efforts in trying to make their SBMCs more organized, enlightened and highly mobilized.